In Vitro Viral Evolution Identifies a Critical Residue in the Alphaherpesvirus Fusion Glycoprotein B Ectodomain That Controls gH/gL-Independent Entry - Melina Vallbracht (American Society for Microbiology, 2021)

(untitled)
The class III fusion protein glycoprotein B (gB) drives membrane fusion during entry and spread of herpesviruses. To mediate fusion, gB requires activation by the conserved gH/gL complex by a poorly defined mechanism.